Proposal: A Political Science Peer Review and Publication Consortium. Issue 1 (28th January 2021) - Gerring, John; Pemstein, Daniel
ABSTRACT: The traditional process of peer review and publication has come under intense scrutiny in recent years. The time seems propitious for a consideration of alternatives in political science. To that end, we propose a Peer Review and Publication Consortium. The Consortium retains the virtues of the traditional peer-review process (governed by academic journals) while also mitigating some of its vices.